High-Performance, Room Temperature, Ultra-Broadband Photodetectors Based on Air-Stable PdSe2 - Liang, Qijie (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.